Financial Literacy Effect and Fintech in Investment Decision Making - Yopy Junianto; Cliff Kohardinata; Diana Silaswara (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
Indonesia is a country that has a fairly good level of investment from year to year, based on KSEI 2020 data. This indicates that Indonesia's business opportunities are quite promising. This increase in investment was also followed by technological developments in the financial sector as we know fintech. The results of this fintech product have been widely used by many groups, especially for investment activities. This is one of the driving points for increasing investment in Indonesia. In general, investments are usually made by people who have sufficient literacy skills. Because various experiences state that someone who has good financial literacy will be able to make good decisions in terms of finances that have both short and long term impacts. However, the current condition has a different pattern where even without financial literacy the cloud community is currently able to invest even if they only get a little information. This research was conducted to see and explain the phenomena that occurred and provide confirmation that the shift in perspective patterns occurred. The result of the research states that financial literacy does not influence a person in making decisions, while fintech is a factor that influences someone in making investment decisions.